EFFECT OF FOLIC ACID ON SOME PHYSIOLOGICAL PARAMETERS IN FEMALE RABBITS TREATED WITH METHOTREXATE - K. A. Hadi; S. D. S. Al-douri; D. H. Hadree (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The present study was carried out to investigate the effect of folic acid (FA) on the hematological picture of female rabbits treated with methotrexate MTX. A total of twenty female rabbits were used in this study. They were at age 4-5 months. Their body weight ranged between 1-1,200 Kgm. All animals were kept under normal condition. its divided in to four groups and each group consist of five animals as follows ( Control group :5 rabbits were received distilled water, Folic acid group : 5 rabbits were received folic acid at 0.07mg/kg body weight daily, Methotrexate group : 5 rabbits were received methtrexate (0.03 mg/kg body weight ) three times a week , folic acid with Methotrexate group : 5 rabbits were received folic acid (0.07 mg/kg body weight) and methotrexate (0.03mg/kg body weight) three times a week. The drugs were given by intubation. The experiment was last for 9 weeks . Blood sample were collected after end of the experiment to study the following hematological parameters: RBCs count, Hb, PCV, RBCs indices (MCV, MCH, MCHC). The group treated with folic acid showed a significant increase P≤0.05 in RBCs count, Hb conc. and PCV% as compared with all other groups. The results of MTX group reveal a high significant decrease in their RBC count, Hb conc., PCV%. At the same time there is a significant increase in MCV, MCH and MCHC indices. The group of animals received FA with MTX showed a good prognosis with health improvement characterized by high significant changes in all studied parameters to return back to their normal values. It was concluded that folic acid is very important for erythropoiesis. MTX treatment induce megaloblastic anemia resulted from inhibition of DNA synthesis in RBCs mainly by folate deficiency. FA administration with MTX correct these changes and the animals return to normal conditions. More work is needed to study the effects of these drugs on other systems in the body.